Bonded - Adeta, Matthew (Literamed Publications Ltd, 2011)
Elizabeth marries Austin when Timothy her first husband is presumed dead. She is at the happiest moment of her marriage to Austin when Timothy re-surface from only God-knows-where. Will she cling to Austin and consider Timothy as one of those past events of her life?...
Keywords: Fiction